1994
DOI: 10.1080/10826069408010098
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Bovine Heart Glycogen Synthase Kinase-3

Abstract: Glycogen Synthase Kinase-3 (GSK-3) was isolated from bovine heart tissue extracts by a procedure involving ammonium sulfate fractionation, followed by chromatography on phosphocellulose, Cibacron blue 3GA-agarose, DEAE-Sephacel, CM-Sepharose, heparin-agarose, myelin basic protein-Sepharose, and LiChrospher 1000 C00-. GSK-3 was identified by its activation of protein phosphatase-1i (PP-1i). The purified enzyme had a specific activity of 25,500 units of protein phosphatase-1i activated/mg protein. The enzyme is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…15,17 Kinase activities of GSK-3␣ and GSK-3␤ are regulated similarly in some cases 18 but differently in other cases. 19,20 Although both isoforms are expressed in the heart, 21 most studies that have been conducted thus far have examined the role of GSK-3␤, possibly because of the general lack of specific reagents for GSK-3␣. Although GSK-3␤ was initially described for its function to inhibit glycogen synthesis through phosphorylation of glycogen synthase, 22,23 it has been revealed that GSK-3␤ regulates a wide range of cellular functions, including metabolism, gene expression, and cytoskeletal integrity 13 ( Figure 1).…”
Section: Gsk-3␤ Is a Proline-directed Serine/threoninementioning
confidence: 99%
“…15,17 Kinase activities of GSK-3␣ and GSK-3␤ are regulated similarly in some cases 18 but differently in other cases. 19,20 Although both isoforms are expressed in the heart, 21 most studies that have been conducted thus far have examined the role of GSK-3␤, possibly because of the general lack of specific reagents for GSK-3␣. Although GSK-3␤ was initially described for its function to inhibit glycogen synthesis through phosphorylation of glycogen synthase, 22,23 it has been revealed that GSK-3␤ regulates a wide range of cellular functions, including metabolism, gene expression, and cytoskeletal integrity 13 ( Figure 1).…”
Section: Gsk-3␤ Is a Proline-directed Serine/threoninementioning
confidence: 99%